Mobile Learning in the EFL Classroom: A Case Study of Teacher Perspectives and Student Experiences - Desliana; Achmad Nurcholis, Ivan (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2025)
This research aims to explore teachers' perspectives regarding the use of mobile learning (m-learning) in English classes. The method used in this research is qualitative with a case study design to explore the use of mobile learning (m-learning) in English classes. Data collection was carried out through 1. Semi-structured interviews. 2 Class Observations 3 Questionnaires were distributed to students to collect data about perceptions, 4. Relevant documentation, such as lesson plans, digital learning materials, technology-based assignments, and evaluation reports, was analyzed to complement the data obtained from interviews and observations. The results of research conducted on teachers' perspectives regarding the use of Mobile Learning in the Classroom can be concluded that the majority of teachers have a positive view of the integration of technology in teaching and learning activities. They feel technology can help create a more interactive, interesting and efficient learning environment. Technology is considered to facilitate access to various learning resources and facilitate collaborative communication between students and teachers.